Bilateral Subluxation of Microspherophakic Lens in a Child with Cohen Syndrome. Issue 1 (2nd January 2023) - Chu, Elizabeth A.; Cummings, Alexandria; Sala, Nicholas; Sala, Nicholas
ABSTRACT: Cohen Syndrome is a rare autosomal recessive condition characterized by facial abnormalities with or without microcephaly, non-progressive intellectual delay, hypotonia, ophthalmic abnormalities, and neutropenia. Due to its low incidence and variable presentation, much about the disorder, including ophthalmic manifestations, is not fully understood. Here, we present the first documented case of a 5-year-old Amish child with Cohen Syndrome who presented with bilateral subluxation of microspherophakic lenses – rare findings themselves, let alone coexisting in a patient with a rare genetic syndrome. The child underwent bilateral lensectomy and is being managed with aphakic spectacles.